The education inside prison: hesitations, limits and possibilities - Graciano, Mariângela; Schilling, Flávia (FCL-UNESP Laboratório Editorial, 2008)
This article aims to analyze the school education offer inside the prison system of São Paulo, based on the thoughts proposed by Foucault (1986) about prison, its aims and functioning mechanisms. What would be the possible place for education inside e prison? These are some questions that surround this debate and draw the central boards of a history which can be qualifi ed, at least, as hesitating, about prison education. In order to found this debate, we discuss the prison education as part of the Education of Young and Adults, its relation to the Human Rights, is legal and administrational outlines and, specifically, the case of school education inside de Women’s Prison of the Capital.